Dedicated CT and MRI Techniques for the Evaluation of the Postoperative Knee - Khodarahmi, Iman; Fishman, Elliot K.; Fritz, Jan (Seminars in Musculoskeletal Radiology, 2018)
Advances in surgical techniques, orthopaedic implant design, and higher demands for improved functionality of the aging population have resulted in a high prevalence of patients with metallic implants about the knee. Total knee arthroplasty, knee-replacing tumor prostheses, and osteosynthesis implants create various imaging artifacts and pose special challenges for the imaging evaluation with computed tomography (CT) and magnetic resonance imaging (MRI). CT artifacts can be effectively mitigated with metal artifact reduction reconstruction algorithms, dual-energy data acquisition with virtual monoenergetic extrapolation, and three-dimensional postprocessing techniques, such as volume and cinematic rendering. Artifacts related to metal implants on MRI can be reduced via optimization of the scan parameters and using advanced techniques such as multi-acquisition variable-resonance image combination, and slice encoding for metal artifact correction.
Keywords: knee; arthroplasty; artifact; computed tomography; magnetic resonance imaging